Impact of attitude, subjective norms, and perceived behavioural control on intention to invest in retail green sukuk among Muslim millennials in Jabodetabek - Ikhsan , Muhammad Ananda; Wulandari, Ries (Universitas Islam Indonesia, 2024)
IntroductionRetail green sukuk is an environmentally friendly investment option for millennials. However, there have not been many studies related to this in the context of millennials in big cities in Indonesia.ObjectivesThis research aims to analyse the impact of attitude, subjective norms, and perceived behavioral control in intention to invest in retail green sukuk among Muslim millennials in Jabodetabek.MethodThis research uses the PLS-SEM (Partial Least Square Structural Equation Modeling) which presents the results of regression analysis relating to testing the relationship between endogenous and exogenous variables. A total of 183 Muslim millennials participate in this research by fulfilling an online questionnaire.ResultsThe results of this research show that these three variables significantly influence Green Sukuk investment interest among Millennial Muslims in Jabodetabek, with a significance value of attitude of 0.669, subjective norm of 0.213, and perceived behavioral control of 0.030.ImplicationsGovernments or other corporations issuing retail green sukuk instruments should focus more on promoting their green initiatives. This will create a positive attitude among millennial investors toward Retail green sukuk instruments.Originality/NoveltyThis study provides insights into the intention to invest in environmentally friendly financial product among Muslim millennials living in large cities in Indonesia.